2016
DOI: 10.2337/db16-0462
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Role for the Type I Interferon Receptor in Virus-Induced Autoimmune Diabetes in Rats

Abstract: The pathogenesis of human type 1 diabetes, characterized by immune-mediated damage of insulin-producing β-cells of pancreatic islets, may involve viral infection. Essential components of the innate immune antiviral response, including type I interferon (IFN) and IFN receptor–mediated signaling pathways, are candidates for determining susceptibility to human type 1 diabetes. Numerous aspects of human type 1 diabetes pathogenesis are recapitulated in the LEW.1WR1 rat model. Diabetes can be induced in LEW.1WR1 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 58 publications
1
16
0
Order By: Relevance
“…Islets from patients recently experiencing onset of T1D exhibit heightened expression of certain ISGs in the islet and peri-islet regions in a manner which is similar to islets infected with virus ( 72 ). Knocking out the type I IFN receptor (IFNAR) in the T1D-susceptible rat strain, LEW.1WR1, protects from T1D, reduces insulitis, and delays onset following poly I:C or virus challenge ( 73 ). Originating with PRR stimulation, aberrant activation of pDCs and genetic mutations in the IFN signaling pathway likely contribute to the IFN signature evident in T1D induction ( 74 ).…”
Section: T1d Displays Interferonopathy-like Qualitiesmentioning
confidence: 99%
“…Islets from patients recently experiencing onset of T1D exhibit heightened expression of certain ISGs in the islet and peri-islet regions in a manner which is similar to islets infected with virus ( 72 ). Knocking out the type I IFN receptor (IFNAR) in the T1D-susceptible rat strain, LEW.1WR1, protects from T1D, reduces insulitis, and delays onset following poly I:C or virus challenge ( 73 ). Originating with PRR stimulation, aberrant activation of pDCs and genetic mutations in the IFN signaling pathway likely contribute to the IFN signature evident in T1D induction ( 74 ).…”
Section: T1d Displays Interferonopathy-like Qualitiesmentioning
confidence: 99%
“…Although knockout of the IFNα receptor (IFNAR) in NOD mice has produced results to the contrary, a preponderance of evidence in preclinical models also supports a pathogenic role for T1-IFN in T1D ( 15 18 ). For example, CRISPR-Cas9 deletion of the IFNAR1 subunit in LEW.1WR1 rats delays spontaneous and polyinosinic-polycytidylic acid–induced diabetes ( 17 ). Additionally, studies revealed that overexpression of IFNα in pancreatic β-cells of nondiabetes-prone mice regulates the onset of diabetes in mice with severe insulitis, whereas expression of IFNβ in islets of NOD mice accelerated autoimmunity ( 19 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…These rats also showed a reduced incidence of poly(I:C)-induced autoimmune diabetes. The splenic cells from the Ifnar1-deficient rats with KRV showed reduced expression of C-X-C motif chemokine ligand (Cxcl) 10 and C-C motif chemokine ligand (Ccl) 5, whereas the expression of Il-1β and Ccl2 was increased [103]. These findings indicate that type 1 IFN-mediated signaling is associated with the development of autoimmune diabetes induced by KRV [103].…”
Section: Ifnar1mentioning
confidence: 91%
“…In IFN-α receptor 1 (Ifnar1)-deficient LEW.1WR1 rats, the incidence of KRV-induced diabetes was shown to be reduced [103]. These rats also showed a reduced incidence of poly(I:C)-induced autoimmune diabetes.…”
Section: Ifnar1mentioning
confidence: 99%